Awareness towards first aid knowledge and emergency preparedness: a survey among hikers in Cameron Highland - Saripuddin, Halimatus Sa'adiah (2019)
Outdoor recreation activities are mainly exposed to injury and illness such as hiking activity. It shows that hikers also involve in injuries and illness as they doing the hiking activity to gain experience and satisfaction when hiking. This study is to determine the awareness towards first aid knowledge and emergency preparedness among hikers in Cameron Highland. Result shows that the hikers have the very basic knowledge of first aid such as the contents of first aid kit, how to be prepared with first aid and some knowledge about the typical injury or illness such as bleeding and do the recovery position. However, they lack of knowledge on how to perform the first aid because they may not confident to do it on site because of lack experience in practicing first aid. Despite that, hikers are aware and knowledgeable with the preparation of emergency such as getting information about the trail, know the emergency contact and bring emergency kit depends on their need during hiking trip. Overall, the study shows that the correlations between variables are moderate. The correlation between first aid knowledge and emergency preparedness with hiking experience and level of first aid are moderately influence each other. The study findings provide information about the importance of first aid knowledge and emergency preparedness among hikers to Department of Forestry in Cameron Highland. Other than that, this study can help to raise the awareness among hikers to care about first aid knowledge and emergency preparedness while doing hiking activity. Thus, these actions will contribute in reducing cases or incidents related to injury and illness in hiking activities.